2015
DOI: 10.1245/s10434-015-4973-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Multiple Lymphatic Basin Drainage in Sentinel Lymph Node-Negative Trunk Melanoma Patients: A Multicenter Study from the Italian Melanoma Intergroup

Abstract: Patients with negative SLN biopsy results have better prognosis when two or more lymphatic basins are identified and analyzed. Further research is required to investigate the mechanisms behind this evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Also in our study, the worse 5-year MSS was also seen in CLND-positive patients compared to CLND-negative patients. Positive SNs in two basins has been published to be worse prognostic factor [19,20]. In our study, only six patients had positive SN in two basins.…”
Section: Discussioncontrasting
confidence: 42%
“…Also in our study, the worse 5-year MSS was also seen in CLND-positive patients compared to CLND-negative patients. Positive SNs in two basins has been published to be worse prognostic factor [19,20]. In our study, only six patients had positive SN in two basins.…”
Section: Discussioncontrasting
confidence: 42%
“…Guidelines for follow-up of stage I–II patients (correctly staged through SLNB or not) differ around centres and usually do not envisage serial screening of visceral sites in the low risk of progression group [10,11] although many patients with an intermediate Breslow thickness melanoma risk progress directly to a visceral site [6,12]. In stage IB/II patients, a more individualised follow-up taking into account the risk factors associated with relapse in visceral sites, which include male gender, trunk site and different SLNB proposal and management [6,7,13,14,15,16], would be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Reported data regarding the prognostic role of histological regression have hitherto been conflicting . A recent paper on a large cohort of stage I–II patients showed a protective role on prognosis in patients with melanoma with histological regression (American Joint Committee on Cancer stage I–II) .…”
Section: Discussionmentioning
confidence: 99%
“…Reported data regarding the prognostic role of histological regression have hitherto been conflicting. 5,[25][26][27] A recent paper on a large cohort of stage I-II patients showed a protective role on prognosis in patients with melanoma with histological regression (American Joint Committee on Cancer stage I-II). 23 At the same time, the discussion regarding SLN performance in thin melanoma with regression has been brought to a conclusion: 28 a meta-analysis has confirmed that histological regression is not a criterion for recommendation of SLN biopsy in thin melanomas.…”
Section: Discussionmentioning
confidence: 99%